Case Report: A Rare Case of Primary Angiosarcoma of the Cervix with a Literature Review - Song Y; Li R; Wang L; Wang H (Dove Medical Press, 2024)
Yuelin Song,1,2,* Ruizhe Li,1,2,* Lifei Wang,3 Hongjing Wang1,2 1Department of Obstetrics and Gynecology, West China Second University Hospital of Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of China; 3Department of Obstetrics and Gynecology, The Fourth Affiliated Hospital Zhejiang University School of Medicine, Yiwu, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongjing Wang, West China Second University Hospital of Sichuan University, No. 20, Section 3, Renmin South Road, Wuhou District, Chengdu, Sichuan Province, 610041, People's Republic of China, Tel +86 181 8060 9060, Email whjscdx@163.comAbstract: Primary angiosarcomas are a rare type of soft-tissue sarcomas that originate from endothelial cells. These sarcomas can develop in any part of the body and have a poor prognosis. However, they are commonly found in the skin of elderly white men, particularly on the scalp and head region. Primary angiosarcoma of the cervix is exceptionally rare. To date, only two cases of this disease have been reported worldwide. The diagnosis of the disease is difficult microscopically, requiring immunohistochemistry and genetic testing to distinguish. We report a recent case, in which the lesion was preoperatively considered a high-grade endometrial stromal sarcoma. A 35-year-old woman presented with vaginal bleeding and cervical erosions. A high-grade endometrial stromal sarcoma involving the cervix was considered and a modified radical hysterectomy was performed with bilateral salpingo-oophorectomy and sentinel lymph nodes resection. The gene diagnosis performed by fluorescence in situ hybridization for YWHAE translocation fusion was negative excluding a YWHAE-translocated high-grade endometrial stromal sarcoma. A primary angiosarcoma of the cervix was finally diagnosed. Primary angiosarcoma of the cervix is rare, and gynecologic pathologists do not know it well, so it is easy to be wrongly considered. Immunohistochemistry and genetic testing help confirm the diagnosis.Keywords: angiosarcoma, case report, cervix, genetic testing, immunohistochemistry